The Covid-19 pandemic and the importance of financing the biotechnology industry in South Africa - Ramazan Uctu; Karen Eksteen (The Journal of Entrepreneurial Finance (JEF), 2022)
Whether it is a government research institution, a public-private partnership, or a private enterprise, the South African biotechnology industry requires funding for the biotechnology industry. Our goal with this research is to look into the role of venture capital (VC) in financing biotech enterprises and demonstrate how VC finance could aid in the development of diagnostic kits and vaccines for Covid-19 or future pandemics in South Africa. The study aims to provide policymakers with a clear image of the importance of funding the biotechnology sector, notably during the Covid-19 period, as recognized by the industry's key players. We employed a questionnaire and an interview survey with the key agencies in biotechnology eco-system to understand the role of biotechnology funding, notably during the Covid-19 pandemic. Overall, participants believe that South Africa's biotechnology lags behind that of other developing countries, but that it has the potential to grow greatly with enablers. It is also regarded immature, fragmented, and fractured due to a lack of financing and a committed organization to organize operations. The South African biotechnology venture capital business is in its infancy stage, risk-averse, conservative in its investment power. In addition, the response time to the pandemic, financial coordination for Covid-19 research, a lack of communication between authorities, and several labs out of operation owing to full-lockdowns have all been noted as problems.
Keywords: 650; Covid-19; Venture capital (VC); financing; biotechnology industry; South Africa